Spiritualitas dan Religiusitas Ki Dalang - Suyanto Suyanto (Institut Seni Indonesia Surakarta, 2022)
The article with the title “Spiritualitas Dan Religiusitas Ki Dalang” (Spirituality and Religiosity of Ki Dalang) is an extract from the paper of the Seminar on Art and Culture of Puppetry 2022, The Culture and Tourism Office of East Java in Surabaya. This paper is the result of reflection on the phenomenon of wayang performing arts in the last decade. Along with the development of technological culture, especially the rapid advancement of social media, it also results to the fast cross-cultural influences between countries; especially for the personality of the artist. The formulation of the discussion in this article focuses on the behavior of the performing artists, especially the art of wayang kulit performances, in Java and Indonesia in general. Data was obtained through observation, either directly or through the YouTube channel. The results of contemplation can be concluded that, when compared with the figures of senior puppeteers in the past, quantitatively the development of young puppeteers is now very rapid. However, when compared in terms of quality, the young dalang, today, seem far below their predecessors, especially in terms of their spirituality and religiosity. As a result, when young puppeteers present their wayang kulit, many things are seen by society as going beyond the norms of decency.